Nicotinamide combined with gemcitabine is an immunomodulatory therapy that restrains pancreatic cancer in mice. Issue 2 (5th November 2020) - Selvanesan, Benson Chellakkan; Meena, Kiran; Beck, Amanda; Meheus, Lydie; Lara, Olaya; Rooman, Ilse; Gravekamp, Claudia
Abstract : Background: Treatments for pancreatic ductal adenocarcinoma are poorly effective, at least partly due to the tumor's immune-suppressive stromal compartment. New evidence of positive effects on immune responses in the tumor microenvironment (TME), compelled us to test the combination of gemcitabine (GEM), a standard chemotherapeutic for pancreatic cancer, with nicotinamide (NAM), the amide form of niacin (vitamin B3 ), in mice with pancreatic cancer. Methods: Various mouse tumor models of pancreatic cancer, that is, orthotopic Panc-02 and KPC (Kras G12D, p53 R172H, Pdx1-Cre) grafts, were treated alternately with NAM and GEM for 2 weeks, and the effects on efficacy, survival, stromal architecture and tumor-infiltrating immune cells was examined by immunohistochemistry (IHC), flow cytometry, Enzyme-linked immunospot (ELISPOT), T cell depletions in vivo, Nanostring analysis and RNAscope. Results: A significant reduction in tumor weight and number of metastases was found, as well as a significant improved survival of the NAM+GEM group compared with all control groups. IHC and flow cytometry showed a significant decrease in tumor-associated macrophages and myeloid-derived suppressor cells in the tumors of NAM+GEM-treated mice. This correlated with a significant increase in the number of CD4 and CD8 T cells of NAM+GEM-treated tumors, and CD4 and CD8 T cell responses to tumor-associated antigen survivin, most likely through epitope spreading. In vivo depletions of T cells demonstrated the involvement of CD4 T cells in the eradication of the tumor by NAM+GEM treatment. In addition, remodeling of the tumor stroma was observed with decreased collagen I and lower expression of hyaluronic acid binding protein, reorganization of the immune cells into lymph node like structures and CD31 positive vessels. Expression profiling for a panel of immuno-oncology genes revealed significant changes in genes involved in migration and activation of T cells, attraction of dendritic cells and epitope spreading. Conclusion: This study highlights the potential of NAM+GEM as immunotherapy for advanced pancreatic cancer.